Old-style mola - Unidentified artist (Colorado State University. Libraries, 1920)
This panel was sewn when mola blouses were loose, sewing was often less refined, and embroidery was less significant to designs.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton, synthetics; 4 layers (red, yellow, black, pink); reverse and direct appliqué.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama